Science, Philosophy and Music - Neuenschwander, Erwin; Bouquiaux, Laurence (Brepols, 2002)
This volume illustrates the old and fruitful dialogue between historians of science and philosophers, as well as new collaborations with artists. It includes two symposia. The first one is on the history of scientific models, the seond is on science and music. It also contains papers on the philosophy of mathematics, physics, technology and politics, but also on Aristotle, Lucretius, Bacon, Le Bon, Spengler, Reichenbach, and Kuhn.